Lifting non-pharmaceutical interventions following the COVID-19 pandemic – the quiet before the storm?. (2nd November 2022) - Oh, Kyu-Bin; Doherty, T. Mark; Vetter, Volker; Bonanni, Paolo
ABSTRACT: Introduction: In the first months of the novel coronavirus (COVID-19) pandemic that begun in 2020, non-pharmaceutical interventions (NPIs) have been adopted worldwide. However, the effects of NPI implementation go beyond slowing the spread of COVID-19. Here, we review the non-intended effects that may have arisen from prolonged application of NPIs. Areas covered: NPIs also affected the epidemiology of other infectious diseases, with unprecedentedly low circulation of several respiratory and gastrointestinal viruses being observed worldwide in 2020. While this was a welcome effect for already strained health-care systems, prolonged low exposure to pathogens may result in an increased pool of individuals susceptible to certain diseases. Out-of-season or unusually intense outbreaks of non-vaccine preventable diseases have already been documented as NPIs were gradually eased. In the context of widespread and important disruptions in national vaccination programs during the early phase of the pandemic, the risk of vaccine-preventable disease resurgence after NPIs are lifted cannot be excluded either. Expert opinion: Awareness must be raised of the risk of vaccine-preventable disease resurgence, and efforts need to be made to mitigate this risk, where possible, by increasing vaccination coverage. Research and regulatory opportunities brought on by the COVID-19 pandemic should be seized. Plain Language Summary: In the first months of the COVID-19 pandemic, the only methods available to slow the spread of the disease were non-pharmaceutical interventions, such as lockdowns, mask wearing, social distancing, school closures, and travel bans. Even after vaccines against COVID-19 became available, combinations of non-pharmaceutical interventions continued to be implemented by most countries, to various extents. Although these measures lowered the number of people who got sick before vaccines and therapies against COVID-19 were available, they also had other consequences for public health. The non-pharmaceutical interventions implemented worldwide have slowed or even stopped the spread of several infectious diseases: since 2020, fewer cases of flu, bronchiolitis, gastroenteritis, and other diseases were recorded compared to pre-pandemic times. This relatively long 2-year period during which people, especially children, were exposed to fewer infections might mean that their immune systems are less prepared to fight these diseases. In addition, vaccination against diseases other than COVID-19 dropped in the early months of the pandemic, meaning that the number of children and adults who are not protected against vaccine-preventable disease has potentially increased. Easing of COVID-19 restrictions has caused a comeback of some diseases against which no vaccine is available, sometimes with more cases than during the pre-pandemic years; there is a risk that this might happen with vaccine-preventable diseases as well. To prevent outbreaks, routine and catch-up vaccinations against other diseases besides COVID-19 should be encouraged and promoted.